Recovery and Utilization of Waste Heat from Cooler Effluent for Preheating Applications - Aulia Indrastuti Sulistiana; Aulia Putri Adinda; Bizan Abdurrahman Hakim; Fionna Rahmatul Izza; Xaviera Fidela Dianingratri (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Maleic anhydride (MA) is an important intermediate for polymers, coatings, and fine chemicals, yet its production through n-butane oxidation remains energy-intensive due to the highly exothermic nature of the reaction. Inefficient heat management leads to excessive utility demand and reduced process performance. This study aims to improve energy efficiency by recovering and reusing waste heat from the cooler effluent for preheating applications. The process is simulated using Aspen HYSYS to compare the basic configuration with a modified design that integrates a recycle stream from the cooler outlet to the heater. The modified configuration demonstrates a significant reduction in external energy consumption, achieving a 43% energy saving compared to the basic process. Net energy decreases markedly, while overall energy efficiency increases to 86%. The recycle stream stabilizes temperature profiles, reduces utility demand, and enhances process reliability. These improvements confirm that waste heat recovery through heat integration provides a practical and effective approach to optimize maleic anhydride production. In conclusion, the modification advances the current state of process design by demonstrating that simple operational changes can deliver substantial energy savings and support sustainable chemical manufacturing. The findings highlight the potential application of waste heat recovery strategies in other exothermic oxidation systems and provide a foundation for future studies on coupling heat integration with advanced separation schemes. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).